Ultra‐widefield fundus photography for radiation therapy planning of ocular tumours. Issue 2 (13th September 2019) - Mathis, Thibaud; Espensen, Charlotte A.; Caujolle, Jean‐Pierre; Herault, Joel; Fog, Lotte S.; Maschi, Celia; Kodjikian, Laurent; Baillif, Stephanie; Kiilgaard, Jens F.; Thariat, Juliette
Abstract: Purpose: The use of planar ultra‐widefield fundus photography (UWF) may result in distortions and inaccurate measurement. The aim of the study was to evaluate the accuracy of UWF instead of the standard narrow field (SF) for the treatment planning phase of ocular tumours. Methods: Distortions between conformal SF and UWF were assessed in 43 patients with choroidal melanoma treated with either proton therapy or brachytherapy. imagej software was used to measure distortion. Results: The median interquartile range ([IQR]) distortion for all cases was 3.7% [1.7–10.8]. For cases with tumours within 6 mm of the optic disc, distortions appeared clinically nonsignificant. For peripheral and/or large tumours, significantly larger distortions were observed on UWF (median 4.4% [2.7–22.6] for tumours ≥6 mm from the optic disc versus 3.3% [1.6–9.9] for those <6 mm, p = 0.04). Images can be subdivided into three groups: minimal distortion (79.1% of eyes), similar level of major distortion for both measured distances (11.6%) and distortion with unequal level of distortion between the measured distances (9.3%). Conclusion: Distortions with UWF appeared minimal in posterior regions of the fundus and increased with the distance from the posterior pole. UWF could therefore be used for treatment planning of ocular tumours as the planned radiation dose to the macula and optic disc are not impacted.